Ending at the Wrong Time: The Financial Reporting Consequences of a Uniform Fiscal Year-End - Li, Zhe; Ye, Kangtao; Zeng, Cheng; Zhang, Bo (The Accounting Review, 2023)
ABSTRACT There is an ongoing debate over uniformity versus flexibility in accounting regulation. This study examines the financial reporting consequences of a rigid accounting rule in China under which the fiscal year-end is uniform for all companies. Using extensive interviews together with large-sample archival analyses, we find that “mismatched” firms—those whose mandated financial reporting cycles are not aligned with their business cycles—exhibit higher levels of absolute abnormal accruals than their nonmismatched counterparts. Further analyses suggest that the negative association between mismatching and financial reporting quality is mainly driven by unintentional estimation errors rather than intentional earnings manipulation. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: M41; M48; K22.